Usage of the National Board of Medical Examiners Subject Test in Psychiatry by U.S. and Canadian Clerkships - Levine, R. E. (Academic psychiatry, 2005)
OBJECTIVE: The authors explored psychiatry clerkship usage of the National Board of Medical Examiners (NBME) Subject Test. METHODS: U.S. and Canadian psychiatry clerkship directors (N=150) were sent an 18-item questionnaire surveying evaluation and remediation practices. RESULTS: Of 111 questionnaires (74%) returned, 76 (69%) reported using the NBME Subject Test. As part of the overall grade, the test was granted a mean weight of 31% and a median weight of 25%. Of 72 clerkship directors who use the test for grading, 42% convert the percentile score and 38% convert the subject score. Of 60 clerkship directors who use the test for passing, 72% convert the raw score (mean=58.3, median=58), and 28% convert the percentile score (mean=12.2th, median=11th percentile). CONCLUSIONS: Most psychiatry clerkship directors use the NBME Subject Test, but no predominant method exists for weighing the test or converting it into a grade.